Conferencia organizada por las JJ.LL. de la barricada de La Torrasa a cargo de Manuel Perez. Board with the aims of the conference. Copied from CNT collection
Conferencia organizada por las JJ.LL. de la barricada de La Torrasa a cargo de Manuel Perez. Board with the aims of the conference. Copied from CNT collection.